Macroscopic effect of the shadow of the electromagnetic field of relativistic electrons; JETP Letters; Vol. 90, iss. 2 - Naumenko G. A. Gennadiy Andreevich; Potylitsyn A. P. Alexander Petrovich; Sukhikh L. G. Leonid Grigorievich; Popov Yu. A. Yuriy Anatolevich; Shevelev M. V. Mihail Viktorovich (2009, 2009)
Title screen